2021
DOI: 10.1080/19476337.2021.1893824
|View full text |Cite
|
Sign up to set email alerts
|

Recent innovations in processing technologies for improvement of nutritional quality of soymilk

Abstract: Soymilk is well known for its health and nutritional benefits and is one of the best plant substitutes for cow milk. Soymilk is high in protein, low in cholesterol, lactose-free, and rich in polyunsaturated fatty acids. The bioactive compounds in soybean contribute to the beneficial effects of soymilk and are reported to exert various bioactivities. With the rising interest in health-conscious lifestyles, the development of soymilk with high nutritional quality is a critical task of the soymilk industry. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 152 publications
0
10
0
Order By: Relevance
“…Although soymilk contains a large amount of particulate matter, it has good electrical conductivity . Compared with the conventional heating method, the free amino acid content in soymilk heated by the ohmic method increases significantly, while the content of mercapto groups and protein surface hydrophobicity decreases significantly . High-voltage pulsed electric field sterilization is a nonthermal processing method that utilizes the principle of dielectric breakdown of strong electric field pulses to inhibit microbial growth in food.…”
Section: Processing Technology Of Plant Protein-based Productsmentioning
confidence: 99%
“…Although soymilk contains a large amount of particulate matter, it has good electrical conductivity . Compared with the conventional heating method, the free amino acid content in soymilk heated by the ohmic method increases significantly, while the content of mercapto groups and protein surface hydrophobicity decreases significantly . High-voltage pulsed electric field sterilization is a nonthermal processing method that utilizes the principle of dielectric breakdown of strong electric field pulses to inhibit microbial growth in food.…”
Section: Processing Technology Of Plant Protein-based Productsmentioning
confidence: 99%
“…Soymilk is a plant‐based milk made from soybean seed and is a popular alternative to dairy milk. The demand for soymilk is increasing annually with the rapid rise in popularity of plant‐based diets (Han et al, 2021). Many studies have investigated the health components and health benefits of soymilk.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Han et al (2021) and Sarangapany et al (2022) showed that a mandatory stage in the production of cow's milk analogues is the extraction of water-and salt-soluble protein fractions from raw materials. First, pre-grinding of raw materials is carried out, followed by the preparation of a suspension and filtering it, to obtain a consistency similar to cow's milk.…”
Section: Introductionmentioning
confidence: 99%
“…Pasteurisation is performed by heat treatment, but Aydar et al (2020) suggest that the use of high temperatures (from 60°C to 130°C) changes the physical, chemical, and organoleptic properties and nutritional value of beverages. Analysing research data by Han et al (2021), an extremely important step in the production of beverages based on plant raw materials is the choice of technological parameters, which is associated with the need to block or break down anti-nutrients: protease inhibitors, lectins (for example, during the use of legumes) specific alkaloids or other substances that can cause protein deposition.…”
Section: Introductionmentioning
confidence: 99%